Sartre e il cinematografo (Materiali di Estetica. Terza serie, 2014)
The article investigates the relationship between French philosopher Jean Paul Sartre and the cinema, with the aim of investigating the different aspects of this elaborate connection. The piece examines and finds Sartre’s philosophical richness in his early works, where he shows his fascination for the tremendous expressiveness of the cinematographic medium. The article crosses also the boundaries of Sartre’s phenomenological analysis of the image condition, without forgetting his following work as author of screenplays, as an important experience that inspired Sartre to change his point of view on the cinema itself. KEYWORDS: movie; flux; screenplay; image